The Evaluation of Higher Order Thinking Skills in English School Nationally Standardized Examination at State Senior High School 6 Semarang - Narwianta, Nanang; Bharati, Dwi Anggani Linggar; Rukmini, Dwi (Universitas Negeri Semarang, 2019)
The English school nationally standardized examination as a means of the assessment of the learning outcomes conduct by educational unit is designed to measure the student`s achievement competencies, to determine student`s graduation from the school, it is very significant to conduct test items evaluation since it gives a clear portrait of the quality of the items and the test as a whole. The purpose of this study was to explain the realization of higher order thinking skills reflected in English school nationally standardized examination at state senior high school 6 Semarang academic year of 2018/2019. The researcher adopted the qualitative descriptive approach using an analysis card to analyze the realization of higher order thinking skills in English school nationally standardized examination test items. The results indicated that HOTS realized in listening, reading, and writing questions. The listening in the form of spoken written, because it is to test listening simultaneously with speaking. There is one listening question categorized into HOTS of level analyzing, in reading the questions belonging to HOTS reach 8 questions that consist of 5 questions of analyzing level and 3 questions of evaluating level. Meanwhile, there is one question of HOTS into level of creating in writing questions. The results also showed the proportion of HOTS comprised 22,22% met the requirement from BNSP that stated in academic year 2018/2019 there is approximately 10-15% of higher order thinking skills test items. Accordingly, this finding reveals that there is still much room for the variation of HOTS levels implemented all skills in English school nationally standardized examination. This study recommends modifying the English school nationally standardized examination by providing them with more questions that include HOTS.